Comparison of Nonalbuminuric and Albuminuric Diabetic Kidney Disease Among Patients With Type 2 Diabetes: A Systematic Review and Meta-Analysis - Shi, Shaomin; Ni, Lihua; Gao, Ling; Wu, Xiaoyan (Frontiers in Endocrinology, 2022)
Background: Diabetic kidney disease (DKD) is one of most common complications of diabetes. Recently, the classical phenotype of DKD, which is characterized by albuminuria preceding renal insufficiency, has been challenged since a subset of diabetic patients with renal insufficiency but without albuminuria has been increasingly reported. However, the available evidence is inconsistent. Thus, the present systematic review will assess and summarize the available data regarding nonalbuminuric diabetic kidney disease (NADKD). Methods: PubMed, Embase and Cochrane were searched for clinical trials related to NADKD. The results were limited to full-text articles published in English, without restrictions on the publication time. The quality of clinical trials was appraised, and the data were extracted. Meta-analysis was conducted using a random-effects model. Descriptive analysis was performed if the data were insufficient. Results: A final total of 31 articles were included in this review. The meta-analysis of 18 studies showed that compared with albuminuric DKD, patients with NADKD were older (MD=1.04 years old, 95% CI [0.52, 1.57], P<0.05); more often women (Male RR=0.74，95% CI [0.68, 0.81], P<0.05); had shorter diabetes duration (MD=-2.9 years, 95% CI [-3.63, -2.18], P<0.05), lower HbA1c levels (MD=-0.34%, 95% CI [-0.42, -.0.25], P<0.05) and lower blood pressure (systolic blood pressure MD=-6.21 mmHg, 95% CI [-9.41, -3.0], P<0.05; diastolic blood pressure MD=-1.27 mmHg, 95% CI [-2.15, 4.0], P<0.05); less frequently experienced diabetic retinopathy (RR=0.58, 95% CI [0.51, 0.67], P<0.05); and less frequently used renin angiotensin aldosterone system (RAAS) inhibitors. The underlying pathology of NADKD might be different from that of the classic phenotype of DKD, which is associated with more advanced tubulointerstitial and vascular lesions but mild typical glomerular lesions. The annual estimated glomerular filtration rate decline tended to be lower in patients with NADKD than in those with albuminuric DKD. The risk for cardiovascular disease, end-stage renal disease and all-cause death was lower for patients with NADKD than patients with albuminuric DKD. Conclusions: The prevalence of NADKD has increased in recent decades, and its characteristics, pathology and prognosis are different from those of albuminuric DKD; thus, diagnosis and treatment strategies should be different. More attention should be given to this phenotype.